Freshman dormitories: west side (1950)
The caption reads: 'A portion of five dormitories are sown in this grouping. Individual rooms have bunk-type beds for two men per room. Each dormitory has central shower and toilet facilities sufficiently large for the needs of the 50 men who live in each unit.' Catalina Hall sits in the bottom right corner of the image.